Comparing methods for measuring the digestibility of miscanthus in bioethanol or biogas processing. Issue 1 (29th June 2016) - Frydendal‐Nielsen, Susanne; Jørgensen, Uffe; Hjorth, Maibritt; Felby, Claus; Gislum, René
Abstract: Lignocellulosic biomass is a candidate for future renewable energy resources. Choice of optimum biomass types and biological conversion techniques requires well‐founded assessment of the digestibility determining the conversion efficiency. The aim of this study was to investigate and evaluate the digestibility of miscanthus samples that were tested using three methods: 3, 5‐dinitrosalicylic acid assay (DNS), anaerobic batch digestion test, and high‐throughput pretreatment and hydrolysis method, including a grinding and hydrothermal pretreatment prior to the analysis (HTPH). The miscanthus samples were expected to have different digestibilities due to maturity stage, dry matter content and the implementation of extrusion as a mechanical pretreatment. The results of the DNS and the biogas batch test methods were highly correlated (R 2 between 0.75 and 0.92), but not with the results of the HTPH method. The DNS and biogas batch test showed that digestibility differed between samples, probably due to the degree of lignification and content of soluble sugars. For the HTPH method, the digestibility for biorefining was the same irrespective of the variation in the other analyses. The HTPH method had higher biomass use efficiency, closely followed by the biogas batch test running for 91 days on the mechanically pretreated biomass. The HTPH method provided information on the overall quantity of carbohydrates that can be made available from a given biomass. Additionally, DNS and biogas batch test visualize the variation in digestibility between biomass types caused by lignification and particle. The study concludes that the choice of evaluation method for miscanthus will depend on the bioenergy conversion method used and that important information on the interaction between physio‐chemical pretreatment and biological accessibility of the biomass can be obtained by comparing the methods. This information will enable sound decisions on the future choice of bioenergy conversion technologies.